STEM education: Impact on mathematics learning outcomes - Ardi Dwi Susandi; Santi Widyawati (Interdisiplinary Journal of Pedagogy and Research in Media Technology, 2025)
Background: The integration of STEM education in mathematics learning aims to enhance students' understanding and application of mathematical concepts in real-world contexts. However, its effectiveness in improving mathematics learning outcomes requires further empirical investigation.Aim: This study examines the impact of STEM education on students' mathematics learning outcomes by comparing STEM-integrated instruction with conventional teaching methods.Method: A quasi-experimental design was employed, involving 52 students divided into an experimental group (STEM-based learning) and a control group (traditional learning). Pre-test and post-test assessments were conducted, and the data were analyzed using statistical tests.Results: The results showed that students in the experimental group had a significantly higher improvement in mathematics learning outcomes compared to the control group. The post-test scores increased by an average of 6.1 in the experimental group, while the control group showed an improvement of only 1.8, t (50) = 4.53, p < 0.05).Conclusion: The findings indicate that STEM education positively influences mathematics learning outcomes by enhancing students’ engagement, problem-solving skills, and conceptual understanding. This study highlights the importance of incorporating STEM-based approaches in mathematics education to optimize student learning outcomes.